Evaluatiun of multi-season intercropping in cassava (Manihot esculenta) - VARUGHESE, KURUVILLA; MEERABAI, M; BABU, K SATHEES (The Indian Journal of Agricultural Sciences, 2013)
Â A multi-season intercropping study based on cassava (Manihot esculenta Crantz) was conducted at Sadanandapuram during 1988-89 and 1989-90. The mean of land-equivalent ratio + area-time equivalent ratio proved superior in measuring the efficiency of the intercroppmg system than land-equivalent ratio,land-equivalent coefficient or area-time equivalent ratio. It could assess both the area and duration of each crop. Was free from problems of overestimation or underestimation of resource utilization and was able to record not only the agronomicÂ  advantage but also the economic advantage in the intercropping system.